IMPROVING NATIONALISM AWARENESS THROUGH SELF LEARNING-BASED MULTIMEDIA SOFTWARE - Putri Kumala Dewi; Supadi Noval Eka Prasetyo (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2020)
The purpose of this study is to develop multimedia developed using Lectora Inspire software based on the Self-Learning method to increase high school students’nationalism awareness. The multimedia development uses the 4D model. To see the improvements students’ nationalism awareness, appropriate media are integrated into construction exposition texts learning and researched using classroom action research. The result is a Self-Learning method multimedia product built using the Lectora Inspire software feasible and inspiring student awareness to internalize the values of nationalism with an average score of 61.8 (cycle 1) and 84.5 (cycle 2).